FORMULATION DEVELOPMENT, OPTIMIZATION & IN VITRO CHARATERIZATION OF LIQUISOLID COMPACTS OF AN OXICAM DERIVATIVE - Kapoor, Devesh; Patel, Manish; Vyas, Ruchi B; Lad, Chaitali (Journal of Drug Delivery and Therapeutics, 2016)
The rationale of the current research was to investigate the in vitro dissolution properties of poorly water soluble piroxicam by utilizing liquisolid technology. Dissimilar liquisoli compacts were formulated using a factorial design to estimate the required quantities of powder and liquid ingredients to fabricate adequately flowable and compressible admixture. About 16 different formulations were developed using factorial design with carriers Neusilin (Magnesium aluminometasilicate)Â and Avicel PH 102, binder PVP K-30 and vehicle PEG-400 as independent variables and Aerosil 200 is used as coating material. The In-vitro drug release from the LSC has used a dependent variable. The empirical method by Spireas and Bolton was applied to calculate the amounts of carrier and coating materials and obtained the improved flow characteristics and hardness by changing the proportion of carrier and coating materials. Liquid solid compacts were fabricated and evaluated for their tabletting properties. Fourier transform infrared (FTIR) analysis, differential scanning calorimetry (DSC) and X- ray powder diffraction (XRPD) were performed. The FTIR spectra showed disappearance of the characteristic absorption band of piroxicam (3338.78 cm-1) in liquisolid formulations which might be attributed to the formation of hydrogen bonding between the drug and liquid vehicle; this resulted in drug dissolution enhancement. A 23 factorial design is used and developed liquid soild compacts using Neusilin LSCN1 to LSCN8 and Avicel PH 102 LSCA1 to LSCA8. The physicochemical characterization of all formulations exhibited well within the specification limits with respect to weight variation, hardness, friability and content uniformity. Â The In-vitro drug release from these liquid soild compacts was evaluated in 0.1 N HCl and the optimized formulation LSCA8 was compared with pure drug (capsule) and physical mixture (tablet). The release studies suggested that the liquisolid tablets outcome in higher release profile than pure active pharmaceutical ingredient and physical mixture due to enhance in surface and wetting properties of the active pharmaceutical ingredient. Liquid solid compacts technique confirmed the enhanced dissolution rate of oxicam derivative, which in turn promotes in enhancing bioavailability. Keywords: Piroxicam, Factorial design, Solubility, Dissolution rate, Avicel PH 102